A New Lease on Life: Preliminary Needs Assessment for the Development of a Survivorship Program for Young Adult Survivors of Cancer in South Texas. Issue 3 (April 2018) - Schmidt, Susanne; Shay, L. Aubree; King, Harriet V.; Buckley, Jordan; Embry, Leanne; Parsons, Helen M.
Abstract : Priorities for young adult survivorship care from the survivors' perspective are not well documented. To address this within our patient population, we conducted a multimethod needs assessment of young adult survivors of pediatric, adolescent, and young adult cancer in South Texas to get a better understanding of the ongoing challenges and priorities for their survivorship needs and related services. Participants were 18 to 39 years at the time of the needs assessment and predominately Hispanic. In an online survey, survivors most commonly cited being concerned about their physical and mental health, long-term treatment effects, recurrence, and health insurance issues. Participants stated that they received critical support from family, friends, and medical staff, but they would like to receive additional support from other cancer survivors through peer mentorship opportunities and survivor retreats/social events. Abstract : Supplemental Digital Content is available in the text.